THE ESCALATION OF MIDDLE EASTERN KURDISTAN POLITICAL CONFLICT IN THE 1980s - Joko Santoso; Fitri Wardani (Arabic Literature Department, 2022)
This paper discusses the escalation of the Kurdish political struggle, which has spread to three Middle Eastern countries: Iran, Iraq, and Turkey. The conflict, which had a lengthy history, escalated in the 1980s. This study examines the historical description of the Kurdish war and the Kurds' efforts to reclaim their identity. Using Talcot's Structural Functionalism theory, the results revealed that Kurds in all three nations had resisted various measures to suppress identity from the 1980s to the present. Unfortunately, the ongoing struggle has earned little worldwide attention. Therefore, further research on the Kurds is required.